A concept analysis of routines for improving health behaviors - Sunny Y. Ruggeri; Amanda Emerson; Cynthia L. Russell (Elsevier, 2023)
Objective: Chronic disease patients often have unhealthy routines, especially when away from health care professionals. These patients need clear guidance about establishing and maintaining routines. This study aimed to synthesize a definition of the concept of routines for improving health behaviors based on its uses in the literature. Methods: We searched CINAHL, Medline, Scopus, and Google Scholar from January to May, 2022 for articles that included definitions of routines in the context of improving health behavior. We applied no date restriction. The systematic analytic method and Rodgers' evolutionary concept analysis method were used. We charted the attributes, antecedents, and consequences of routines for improving health behaviors, analyzed their uses in the literature, and synthesized the results in a definition of the concept. Result: At total of 24 articles were included. Attributes of the concept were repeated patterns, controllable by the patient, goal-oriented health, and integration into an overarching lifestyle. Antecedents were individual characteristics and environmental factors. Consequences were psychological, physical, and social well-being at individual and environmental levels. Conclusion: This clarified definition of routines for improving health behaviors will provide a starting point for future research and, eventually, a basis for clinical nursing interventions to support patients in developing and maintaining healthy routines to promote better patient outcomes.